Star authors : literary celebrity in America - Moran, Joe, 1970- (Pluto Press, 2000)
In America, authors are as likely to be seen on television talk shows or magazine covers as in the more traditional settings of literary festivals or book signings. Is this literary celebrity just another result of 'dumbing down'? Yet another example of the mass media turning everything into entertainment? Or is it a much more unstable, complex phenomenon? And what does the American experience tell us about the future of British literary celebrity?In Star Authors, Joe Moran shows how publishers, the media and authors themselves create and disseminate literary celebrity. He looks at such famous contemporary authors as Toni Morrison, J.D. Salinger, Thomas Pynchon, Don DeLillo, John Updike, Philip Roth, Kathy Acker, Nicholson Baker, Paul Auster and Jay McInerney. Through an examination of their own work, biographical information, media representations and promotional material, Moran illustrates the nature of modern literary celebrity. He argues that authors actively negotiate their own celebrity rather than simply having it imposed upon them - from reclusive authors such as Salinger and Pynchon, famed for their very lack of public engagement, to media-friendly authors such as Updike and McInerney. Star Authors analyses literary celebrity in the context of the historical links between literature, advertising and publicity in America; the economics of literary production; and the cultural capital involved in the marketing and consumption of books and authors.